PENGARUH TEKTONIK PADA LEMBAH SUNGAI CILIWUNG DENGAN PENGUKURAN GPS- RTK BERDASARKAN NILAI VALLEY-FLOOR RATIO (Vf) - Witjahjati, Retno; Sukiyah, Emi; Winantris, .; Arya, Pulung P; Nugroho, Bani (Fakultas Teknik Geologi Universitas Padjadjaran, 2018)
Most of Jakarta's Special Capital Region (DKI) has relatively flat topography covered by alluvial deposit. Alluvial deposit derives from rock deformation of volcanic activity in the south, and also coastal deposits at the north part. The upstream rivers located in hilly, mountainous terrain, as well as through sloping hills to the lower plains downstream. The relatively rapid flow velocity in the upstream forms the parallel pattern and the downstream are slowly forming a sub dendritic pattern until it empties into the Jakarta Bay. Ciliwung River is one of 13 rivers passing through DKI Jakarta.The morphology of DKI Jakarta area is formed by exogenous energy caused by highly intensive sedimentation and human activities. In addition, there is also endogenous energy to produce folds and fracture structures. The presence of endogenous power results from the convergence interaction between the Indian-Australian Ocean Plate and the Eurasian Plate.This research was conducted to find out the influence of endogenous power in the form of tectonic control on the pattern of landscape shape in DKI Jakarta. The manifestation of these endogenous influences can be seen in the morphological formation in the Ciliwung River. The method used is calculated of morphometry with a value of the VF - ratio (Valley Floor Ratio) from topographic measurement using GPS-RTK device (Global Position System - Real Times Kenematic). Measurements were made as many as 7 trajectories on the river banks in order to know the difference of elevation on the left and right side. Based on the calculation, the Vf value ranged from 1.65 to 3.47. Through these results, it can be concluded that the morphology of DKI Jakarta is controlled by tectonic process with medium category.